Type I interferon correlates with serological and clinical manifestations of SLE. Issue 12 (20th April 2005) - Dall'Era, M C; Cardarelli, P M; Preston, B T; Witte, A; Davis, J C
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease affecting multiple organ systems triggered by the production of autoantibodies. Previous clinical studies in humans and murine models suggest that type I interferons (IFNs) are important for the initiation and potentiation of SLE activity. Methods: 65 consecutive patients with SLE were identified from the University of California, San Francisco Lupus Clinic with moderate-severe disease activity. 94 serological samples were collected. Type I IFN levels and the ability of plasma to induce expression of several surface markers of dendritic cell maturation were measured. Results: Type I IFN levels correlated with the presence of cutaneous manifestations, and there was a trend towards correlation with renal disease. No correlation was found between type I IFN levels and neurological disease. Type I IFN levels correlated positively with the SLEDAI score and anti-dsDNA levels and inversely with C3 levels. Interestingly, type I IFN levels were highest in African American patients. SLE plasma also induced the expression of MHC class I, CD38, and CD123 on monocytes, and was blocked by the addition of a monoclonal antibody to IFNAR1. Conclusions: The pathogenic role of type I IFN is suggested by the induction of cell surface markers for dendritic cell maturation. The potential therapeutic utility of antibodies directed to either type I IFN or IFNAR1/IFNAR2 may be of interest in further studies.